2021
DOI: 10.1080/21655979.2021.1952772
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of chemokine (C-X-C motif) ligands CXCL1 and CXCL3 as prognostic biomarkers in rectal adenocarcinoma: evidence from Gene Expression Omnibus (GEO) analyses

Abstract: Rectal cancer is a life-threatening disease worldwide. Chemotherapy resistance is common in rectal adenocarcinoma patients and has unfavorable survival outcomes; however, its related molecular mechanisms remain unknown. To identify genes related to the initiation and progression of rectal adenocarcinoma, three datasets were obtained from the Gene Expression Omnibus database. In total, differentially expressed genes were analyzed from 294 tumor and 277 paracarcinoma samples from patients with rectal cancer. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Investigations have indicated that CRC patients with high proportions of peripheral blood neutrophils showed a poorer response to radiotherapy than patients with low numbers of neutrophils [80]. This also applies to CRC tumor tissues [81, 82]. Other studies have found that CRC tumors with higher neutrophil-lymphocyte ratios are insensitive to radiation [8389], and similar interpretations have been drawn for the cell proportions in the peripheral blood [9095].…”
Section: Tumor-infiltrating Immune Cellsmentioning
confidence: 83%
“…Investigations have indicated that CRC patients with high proportions of peripheral blood neutrophils showed a poorer response to radiotherapy than patients with low numbers of neutrophils [80]. This also applies to CRC tumor tissues [81, 82]. Other studies have found that CRC tumors with higher neutrophil-lymphocyte ratios are insensitive to radiation [8389], and similar interpretations have been drawn for the cell proportions in the peripheral blood [9095].…”
Section: Tumor-infiltrating Immune Cellsmentioning
confidence: 83%
“…We confirmed upregulated chemokines, including CXCL1 and CXCL3, which are associated with inflammation and progression of a certain cancer. 37 The expression of CXCL3 was higher in peri-implantitis than in periodontitis, suggesting that peri-implantitis is a more severe type of inflammation. The function of matrix metalloproteinase (MMP) during the progression of periodontitis and peri-implantitis was well characterized by its extracellular matrix protein degradation function, as well as highly upregulated MMP9, MMP13, and ADAM12 expression in both diseased tissues than in healthy controls.…”
Section: Discussionmentioning
confidence: 96%
“…60 As for miRNAs, expression of has-miR-1-3p and has-miR-29a-3p were found in immune-related pathways in cardiomyopathy and cancer. 61,62 63 Clinically, their protective immunomodulatory and antiviral effects can be of great help in adverse events related to COVID-19, such as ARDS. 64,65 Much evidence has also accumulated that 11-cis-retinal plays a vital role in diabetic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, KLF13 is also involved in the neuropathology of diet‐induced obesity and has a possible link with diabetes 60 . As for miRNAs, expression of has‐miR‐1‐3p and has‐miR‐29a‐3p were found in immune‐related pathways in cardiomyopathy and cancer 61,62 . Nevertheless, their regulatory role in DFU and COVID‐19 has been limited to date.…”
Section: Discussionmentioning
confidence: 99%